Strategi Peningkatan Animo Masyarakat Terhadap Sekolah Melalui Optimalisasi Layanan Humas Sekolah - Saputra, Bagus Rachmad; Shahbana, Elvia Baby; Satria, Rachmat Rachmat (Universitas Negeri Surabaya, 2021)
Participation cannot be released in an effort to improve the quality of schools through educational programs that are planned and implemented by schools. The involvement of students' parents as users of educational services offered by schools as well as stakeholders needs attention from the school. In order to accommodate the expectations of the community towards the school. The research and writing of this article aims (1) the implementation of school collaboration activities with parents, (2) the implementation of school collaboration activities with the surrounding community, (3) the strategy of increasing public interest in the Kalam Kudus Christian High School Surakarta. The research method uses a qualitative research approach where data is obtained through interviews, participatory observation in schools, and documentation studies. Furthermore, the data obtained were analyzed through triangulation techniques. The results of this study are (1) the form of school collaboration activities with parents, (2) the form of school activities involving the community around the school, and (3) the efforts of the school in increasing public interest in the school.